Analysis of Facial Expressions Made While Watching a Video Eliciting Compassion. Issue 2 (April 2020) - Kanovský, Martin; Baránková, Martina; Halamová, Júlia; Strnádelová, Bronislava; Koróniová, Jana
The aim of the study was to describe the spontaneous facial expressions elicited by viewers of a compassionate video in terms of the respondents' muscular activity of single facial action units (AUs). We recruited a convenience sample of 111 undergraduate psychology students, aged 18-25 years ( M = 20.53; SD = 1.62) to watch (at home alone) a short video stimulus eliciting compassion, and we recorded the respondents' faces using webcams. We used both a manual analysis, based on the Facial Action Coding System, and an automatic analysis of the holistic recognition of facial expressions as obtained through EmotionID software. Manual facial analysis revealed that, during the compassionate moment of the video stimulus, AUs 1 = inner-brow raiser, 4 = brow lowerer, 7 = lids tight, 17 = chin raiser, 24 = lip presser, and 55 = head tilt left occurred more often than other AUs. These same AUs also occurred more often during the compassionate moment than during the baseline recording. Consistent with these findings, automatic facial analysis during the compassionate moment showed that anger occurred more often than other emotions; during the baseline moment, contempt occurred less often than other emotions. Further research is necessary to fully describe the facial expression of compassion.